BERPETUALANG DENGAN CAHAYA: MENINGKATKAN HASIL BELAJAR SAINS SISWA KELAS V MELALUI PROJECT BASED LEARNING (PJBL) - Aisa, Siti; Sukartiningsih, Wahyu; Marsyiah, Siti; Maulita Zuliyawati, Erika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to enhance the science of light and its properties learning outcomes of class V students at SD Negeri Pradah KaliKendal I Surabaya through the implementation of the Project Based Learning (PjBL) paradigm. Planning, action, observation, and reflection are the four steps of the two cycles that make up the Classroom Action study (PTK) study methodology. There were twenty-five pupils in class V who served as the research subjects. While data analysis techniques employ descriptive analysis, data gathering techniques include observation sheets, testing, and documentation. The average proportion of students' learning outcomes has grown, according to the research findings. The student learning outcomes score was 40% incomplete in the Pre-Cycle before to treatment, 72% in the First Cycle, and 72% in the Second Cycle.